2011
DOI: 10.1111/j.1540-8159.2010.02997.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent Brugada Syndrome and Wolff‐Parkinson‐White Syndrome: What Is the First Clinical Presentation?

Abstract: The coexistence of Brugada syndrome and Wolff-Parkinson-White (WPW) syndrome is a very rare phenomenon. We describe a 31-year-old patient without any previous cardiac disorder admitted to our hospital due to palpitations and concomitantly diagnosed as WPW syndrome and treated with radiofrequency catheter ablation. He was later diagnosed with Brugada syndrome and followed-up 2 years without any symptoms. We discuss other previously reported cases in literature, in which these two conditions exist simultaneously. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…By reviewing literature, including the present patient, we found that only 8 similar cases have ever been reported 6, 16. Seven patients are men (87.5%) with age between 23 and 58 years (mean age 37.0 ± 12.9 years).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…By reviewing literature, including the present patient, we found that only 8 similar cases have ever been reported 6, 16. Seven patients are men (87.5%) with age between 23 and 58 years (mean age 37.0 ± 12.9 years).…”
Section: Discussionmentioning
confidence: 55%
“…Although the cases of BrS or WPW syndrome together with PAF have been reported in several medical literatures,4, 5 BrS with WPW syndrome has also been noticed around the world;6, 7, 8, 9, 10, 11 and a patient with the combination of all these and a comprehensive medical history with long-term follow-up is rare. AF is the most usual atrial arrhythmia in BrS, with an incidence between 6% and 53%, 12 because the substrate responsible for the development of ventricular arrhythmias may also contribute to atrial arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The association between BS and ventricular preexcitation was first described in 2001 by Eckardt et al . Subsequently, six other cases of this association have been reported . The uniqueness of this case was that the typical ST segment elevation occurred only after administration of propafenone for pharmacological treatment of WPW syndrome.…”
Section: Discussionmentioning
confidence: 68%
“…Another question that arises is whether these patients with both syndromes would be more susceptible to arrhythmias and SCD, and could be candidates to receive a prophylactic ICD. Of the seven cases reported, four patients received an ICD, two patients refused the implant, and one patient received no ICD because he was asymptomatic and ventricular tachycardia (VT) or VF was not induced at EPS. In individuals without BS, a sustained polymorphic VT or VF is exceptionally induced.…”
Section: Discussionmentioning
confidence: 99%
“…In up to 20% of patients, AF or supraventricular tachycardia due to atrioventricular (AV) nodal re-entry or Wolff-Parkinson-White syndrome have been reported. [10]…”
Section: Ecg Patternmentioning
confidence: 99%